Research on agricultural development in East Africa - McLoughlin, Peter F. M.; Agricultural Development Council (New York : The Agricultural Development Council, 1967)
The monograph's purpose is to classify and evaluate research on rural development in East Africa (Kenya, Uganda, Tanzania), and to indicate areas and priorities of future research
Includes bibliographical references: p. 106-108.
osc 31/01/2019
Loans
Keywords: Agriculture; Africa, East